Active Suspension Control Using Multiorder PID Controller - Ridzuan, Mohd Rasyidi (UTeM, 2016)
This study investigates the propose controller for active suspension system to improve ride comfort of the vehicle. The main content of this study is the development and application of the multiorder Proportional-Integral-Derivative (MOPID) control scheme, and the investigation of the control system ability to provide improvement in vehicle ride comfort. The multiorder Proportional-Integral-Derivative (MOPID) are arranged in a separated control loops called the outer loop controller, which is used to amplify the disturbance from the road input and reduce unnecessary vehicle motions and the inner loop controller that is produced the signal to the active suspension system to produce the force by force actuator. The performance of the proposed controller is compared to the conventional PID controller and the passive suspension system. Simulation studies are shown in time domain simulation produce from Matlab/Simulink software. From the simulation, it shows that the proposed control scheme is able to provide improvement in terms of body vertical displacement and body vertical acceleration. The development of the multiorder PID is also easy to implement in practice based to its simple controller structure.